Penerapan Metode Buzz Group Discussion untuk Meningkatkan Kemampuan Kerja Sama Siswa Kelas X SMA Negeri 1 Tanjung Batu - Ummul Padlah; Halimatussakdiah; Ibnu Rozali (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study was motivated by the low cooperation skills of students in Islamic Religious Education learning due to the dominance of conventional teaching methods, which caused students to be passive and less actively involved in the learning process. Therefore, the Buzz Group Discussion method was implemented to encourage student interaction and participation. This study aimed to determine students’ cooperation skills before and after the implementation of the Buzz Group Discussion method and to analyze its effect on improving students’ cooperation skills. The study used a quantitative approach with a One Group Pretest-Posttest Design. The subjects of this research were 36 tenth-grade students at SMA Negeri 1 Tanjung Batu. Data were collected through questionnaires, observations, and documentation, then analyzed using descriptive statistics and the Paired Sample t-Test. The results showed that students’ cooperation skills improved after the implementation of the Buzz Group Discussion method. The average score increased from 72.36 on the pretest to 92.61 on the posttest, with an increase of 20.25 points. The hypothesis test showed a significance value of 0.000 < 0.05, indicating that the Buzz Group Discussion method had a significant effect on students’ cooperation skills. Therefore, it can be concluded that the implementation of the Buzz Group Discussion method positively improved students’ cooperation skills in Islamic Religious Education learning